Human autoantibodies against the 54 kDa protein of the signal recognition particle block function at multiple stages - Römisch, Karin (BioMed Central, 2006)
The 54 kDa subunit of the signal recognition particle (SRP54) binds to the signal sequences of nascent secretory and membrane proteins and it contributes to the targeting of these precursors to the membrane of the endoplasmic reticulum (ER). At the ER membrane, the binding of the signal recognition particle (SRP) to its receptor triggers the release of SRP54 from its bound signal sequence and the nascent polypeptide is transferred to the Sec61 translocon for insertion into, or translocation across, the ER membrane. In the current article, we have characterized the specificity of anti-SRP54 autoantibodies, which are highly characteristic of polymyositis patients, and investigated the effect of these autoantibodies on the SRP function in vitro. We found that the anti-SRP54 autoantibodies had a pronounced and specific inhibitory effect upon the translocation of the secretory protein preprolactin when analysed using a cell-free system. Our mapping studies showed that the anti-SRP54 autoantibodies bind to the amino-terminal SRP54 N-domain and to the central SRP54 G-domain, but do not bind to the carboxy-terminal M-domain that is known to bind ER signal sequences. Nevertheless, anti-SRP54 autoantibodies interfere with signal-sequence binding to SRP54, most probably by steric hindrance. When the effect of anti-SRP autoantibodies on protein targeting the ER membrane was further investigated, we found that the autoantibodies prevent the SRP receptor-mediated release of ER signal sequences from the SRP54 subunit. This observation supports a model where the binding of the homologous GTPase domains of SRP54 and the α-subunit of the SRP receptor to each other regulates the release of ER signal sequences from the SRP54 M-domain.